Pharmaceuticals and their transformation products in agroecosystems: Threats to plant-soil sustainability - Garazade, Narmin; Nightingale, John; Kay, Paul; Varank, Gamze; Carter, Laura J. (TAYLOR & FRANCIS INC, 2026)
Amending soils with biosolids or animal manures enhances nutrient availability, while wastewater irrigation enhances crop productivity in water-scarce regions. However, the application of these practices can introduce biologically active pharmaceuticals into agricultural soils, where they can be transformed into persistent and potentially more toxic products. In this review, we synthesize existing knowledge on the occurrence, fate, and behavior of pharmaceutical transformation products and metabolites in soil and plant systems. We summarize detection of specific transformation products in soils and edible plant tissues, analyze and assess their persistence in the environment and bioaccumulation, and quantify their mobility and uptake in comparison to parent compounds. We also evaluate the limited data on toxicological effects to ecosystems and human health, and explicitly note the substantial knowledge gaps in the literature on field-based studies. In summary, this synthesis of findings in soil and plants emphasizes the need to incorporate pharmaceutical transformation products and metabolites into risk assessments to protect food safety and agricultural sustainability.
Keywords: Agricultural sustainability; emerging contaminants; metabolites; pharmaceuticals; transformation products; Dr. Taicheng An; PERSONAL CARE PRODUCTS; TREATED WASTE-WATER; ADVANCED OXIDATION PROCESSES; CRESS LEPIDIUM-SATIVUM; LIQUID-CHROMATOGRAPHY; AGRICULTURAL SOILS; RISK-ASSESSMENT; ENVIRONMENTAL FATE; METABOLIC PATHWAYS; DRUG-METABOLISM; Engineering; Environmental Sciences & Ecology